IMPLEMENTASI ALGORITMA HUFFMAN PADA KOMPRESI FILE WAVEDENGAN MENGGUNAKAN BORLAND DELPHI - Yusuf Sumaryana (JUTEKIN (Jurnal Teknik Informatika), 2014)
One sound file format that is widely used in the Windows operating system is the Wave format (*. WAV). Wave is a coarse file format (raw format) where the direct sound signal recorded and quantized into digital data. So a recorded track CD -quality audio it will require the storage media is large enough, and therefore we need a software that can reduce the file in order to save storage media.The aim in this paper is to determine how the Huffman algorithm used in the compression wave files, and can generate a software that can compress a wave file, which saves storage capacity.The steps taken in this are problem solvers library research or library research, to gather a variety of information related to the structure of the wave file and Huffman algorithms, and so designing a program interface.File wave which has a large capacity can be compressed with the Huffman algorithm can generate a range ratio ranged from 20 % to 40 %. So it can be said with a compression ratio of Huffman's algorithm has been said to be good in terms of compressing files, especially files Wave.Keyword : Sound, Wave, Huffman's Algorithm.